Advanced applications of smart electrospun nanofibers in cancer therapy: With insight into material capabilities and electrospinning parameters - Tayebi-Khorrami, Vahid; Rahmanian-Devin, Pouria; Fadaei, Mohammad Reza; Movaffagh, Jebraeel; Askari, Vahid Reza (International journal of pharmaceutics: X, 2024)
Cancer remains a major global health challenge, and despite available treatments, its prognosis remains poor. Recently, researchers have turned their attention to intelligent nanofibers for cancer drug delivery. These nanofibers exhibit remarkable capabilities in targeted and controlled drug release. Their inherent characteristics, such as a high surface area-to-volume ratio, make them attractive candidates for drug delivery applications. Smart nanofibers can release drugs in response to specific stimuli, including pH, temperature, magnetic fields, and light. This unique feature not only reduces side effects but also enhances the overall efficiency of drug delivery systems. Electrospinning, a widely used method, allows the precision fabrication of smart nanofibers. Its advantages include high efficiency, user-friendliness, and the ability to control various manufacturing parameters. In this review, we explore the latest developments in producing smart electrospun nanofibers for cancer treatment. Additionally, we discuss the materials used in manufacturing these nanofibers and the critical parameters involved in the electrospinning process. [Display omitted] •Smart electrospun nanofibers are pivotal in cancer therapy.•They respond to temperature, pH, magnetic, light, or a combination of these.•Their stimuli-responsive nature minimizes side effects.•Electrospinning parameters shape nanofiber traits significantly.•Material and polymer selection is critical for stimuli-sensitive nanofibers.